Estudo da resistência à corrosão de aços inoxidáveis martensíticos utilizados em rolos de lingotamento contínuo - Lima, Darley da Silva (2020)
The corrosion resistance study of the martensitic stainless steels AISI 414 and AISI 415, used as continuous caster roll coatings, was carried out to study the influence of temperature and NaCl concentration on the corrosives processes by the electrochemicals techniques of the open circuit potential monitoring, potentiodynamic polarization, impedance spectroscopy and chronoamperometry. Pitting and crack corrosion are the most frequent and metal anodic dissolution is accelerated within the discontinuities promoted by the presence of NaCl, which is present in the cooling water. Due to the working conditions, it is essential to use coatings with high mechanical resistance, wear and good resistance to corrosion. Martensitic stainless steels are the most used industrially, but they are susceptible to exhibit fragile regions due to the phenomenon of sensitization and percentage of δ (delta) ferrite present in the microstructure. The electrochemical analyzes were performed with NaCl electrolytes at concentration 150, 300 and 450 ppm for temperatures of 25, 40 and 55oC. Additionally, a study was performed of the vickers microhardness profile between base metal / cladding interface / metal coating, characterizing the influence of ferrite δ in the strength and hardness of the coating. In order to analyze the microstructure and surface morphology, characterization were performed using optical and scanning electron microscopes. As a general trend, temperature presented itself as the variable that most influenced the progression of the corrosive attack. In all electrochemical tests performed, the steel AISI 415 showed better behavior in relation to corrosion resistance for all analyzes when compared to the steel AISI 414. The hardness of the coating deposit, for steel AISI 414, was the most affected by the presence of δ ferrite, presenting the lowest microhardness values for the region.